2021
DOI: 10.1371/journal.pone.0261785
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for suicidal ideation and suicide attempt among medical students: A meta-analysis

Abstract: Background Medical training poses significant challenge to medical student wellbeing. With the alarming trend of trainee burnout, mental illness, and suicide, previous studies have reported potential risk factors associated with suicidal behaviours among medical students. The objective of this study is to provide a systematic overview of risk factors for suicidal ideation (SI) and suicide attempt (SA) among medical students and summarize the overall risk associated with each risk factor using a meta-analytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 54 publications
2
26
0
6
Order By: Relevance
“…Despite the studies in China being conducted earlier, the students were exposed to constant sources of stress during the pandemic, and they would have developed coping strategies to overcome stress complications such as depression and related suicidal behaviors. Smoking cigarettes and/or marijuana was associated with suicidal ideation, a finding consistent with other studies prior to the COVID-19 pandemic ( 58 ). Substance use increased during the COVID-19 pandemic and led to multiple mental challenges, including suicide ( 59 63 ).…”
Section: Discussionsupporting
confidence: 90%
“…Despite the studies in China being conducted earlier, the students were exposed to constant sources of stress during the pandemic, and they would have developed coping strategies to overcome stress complications such as depression and related suicidal behaviors. Smoking cigarettes and/or marijuana was associated with suicidal ideation, a finding consistent with other studies prior to the COVID-19 pandemic ( 58 ). Substance use increased during the COVID-19 pandemic and led to multiple mental challenges, including suicide ( 59 63 ).…”
Section: Discussionsupporting
confidence: 90%
“…The same inconsistent results were observed when exploring relationship between study pressure and suicidal ideation among college students. Seo found that study pressure was a risk factor for suicide ideation ( 16 ). Wang revealed that increased study pressure and burden was associated with a higher risk of suicidal ideation ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other periods, college students experience a critical transition period, which is characterized by the stress from adapting to a new environment, losing and rebuilding social support systems. Therefore, besides aforementioned risk factors, study pressure, having been bullied, academic difficulties, and substance use were suggested by previous studies as risk factors for suicidal ideation among college students ( 16 20 ). However, the results of which predictors are most useful were inconsistent due to different sample populations, statistical methods and questionnaires.…”
Section: Introductionmentioning
confidence: 98%
“…대학생의 자살위험은 다양한 심리사회 요인들로 설명 될 수 있으며, 주요한 위험요인 중 하나는 우울과 같은 정신건강 문제이다 [7][8][9][10][11]. 실제, 우울증을 경험하는 대 학생은 그렇지 않은 경우에 비해 자살사고 위험이 6.87 배, 자살시도 위험이 9.34배 높았으며 [8], 무망감, 무력 감, 무가치감과 같은 우울 증상은 청소년 및 성인 초기 자살시도 동기의 42.8%를 설명하였다 [10].…”
unclassified
“…대학생의 자살위험은 다양한 심리사회 요인들로 설명 될 수 있으며, 주요한 위험요인 중 하나는 우울과 같은 정신건강 문제이다 [7][8][9][10][11]. 실제, 우울증을 경험하는 대 학생은 그렇지 않은 경우에 비해 자살사고 위험이 6.87 배, 자살시도 위험이 9.34배 높았으며 [8], 무망감, 무력 감, 무가치감과 같은 우울 증상은 청소년 및 성인 초기 자살시도 동기의 42.8%를 설명하였다 [10]. 더불어 관계 갈등, 소외 및 외로움과 같은 대인관계 문제도 대학생의 자살위험을 높일 수 있는 요인인데 [9,10], 예를 들어, 타 인과 의미 있는 관계를 맺고 있지 못하다는 인식인 좌절 된 소속감은 자살의 대인관계 이론(interpersonal theory of suicide)에서 상정하는 자살사고의 주요 위험 요인이다 [12].…”
unclassified